Determinação da eficácia de probióticos e prebióticos contra o desafio horizontal de Salmonella Heidelberg em frangos de corte - Matté, Fabrizio (2015)
Salmonella is one of the leading foodborne pathogens. Among the serotypes, Salmonella Heidelberg (SH) has been standing out in the creation of chickens because of the fact of having a large number of reservoirs, presenting nonspecific serotypes and multidrug-resistant strains to antibacterial. Eubiótics additives such as probiotics and prebiotic are being evaluated not to fully replace antibiotics, but to be a strategic tool to reduce their use. This study aimed to evaluate the effect of two probiotics and prebiotic against a horizontal challenge Salmonella Heidelberg in broilers through count CFU/g of cecal contents and under the zootechnical parameters. 224 chickens were used, distributed in 16 boxes of 2m2 every. The chickens were grouped into 4 treatments with 4 replications of 14 chickens every boxe, a total of 56 chickens per group on a design in casualized blocks (DBC). It has been tested a prebiotic consisting mananoligossacarids (MOS) associated with a fermentation of Bacillus subtilis (Pre1) provided on the 2 and 14 days of age by oral gavage, and two probiotics, one composed of 11 Lactobacillus strains (Pro1) provided at 1, 17 and 18 days, in drinking water, and another composed of Bacillus subtilis spores (Pro2) supplied the feed all through the experimental period. Inoculation with SH was at 2 days of age using (1,0x106 UFC/chicken) by oral gavage for 4 chicks denominated contaminated by boxe, the other 10 chicks were denominated non contaminated to evaluate the horizontal contamination. The chickens were weighed a weekly basis, and feed consumption calculated from each group. At 28 days of age, 40 poultry non contaminated per group were sacrificed and we evaluated the counts CFU/g of cecal content. The results obtained for the count of CFU/g of cecal content in every Pre1 treatment, Pro1 and Pro2 no significant differences (P>0.05) compared to the control group. The zootechnical results presented only significant differences (P<0.05) feed conversion, with results favorable to the use of probiotics and prebiotics in late periods of growth of the poultry 14 to 21 and from 21 to 28 days.